Evolution of Precipitates and Microhardness of L-PBF Inconel 625 Through Relevant Thermal Treatment - Tahmina Keya; Ralf D. Fischer; Mohanish Andurkar; Scott M. Thompson; Valentina O’Donnell; John Gahl; Barton C. Prorok (Alloys)
Laser powder bed fusion (L-PBF) is a metal additive manufacturing (AM) technique that produces a unique microstructure significantly different from wrought microstructure. Inconel 625 (IN625) is an alloy widely used to manufacture complex parts, but it comes with its own unique challenges. The alloy is prone to precipitation under elevated temperatures, which makes designing suitable heat treatment to tailor the desired microstructure and mechanical properties critical. Traditional heat treatment for wrought IN625 cannot be applied to L-PBF IN625; therefore, it is vital to understand the evolution of precipitates on the way to complete recrystallization. This study focuses on these precipitates in IN625 produced by the L-PBF technique. Heat treatments at 700 °C, 900 °C, and 1050 °C were performed separately to encourage the precipitation of strengthening γ″, the detrimental δ phase, and the dissolution of precipitates, respectively. γ″ precipitates were found in the as-printed condition and at 700 °C. δ precipitates were detected at 700 and 900 °C. Carbides and Al-rich oxides were observed in all conditions of L-PBF IN625. Texture analysis showed grain growth along the build direction with strong (100) texture at temperatures up to 900 °C. Weak and random texture with equiaxed grains was observed at 1050 °C, which is similar to wrought IN625.